Community, seriality and the state of the nation: British and Irish television series in the 21st century - Lusin, Caroline; Haekel, Ralf (Narr Francke Attempto, 2019)
Since the turn of the 21st century, the television series has rivalled cinema as the paradigmatic filmic medium. Like few other genres, it lends itself to exploring society in its different layers. In the case of Great Britain and Ireland, it functions as a key medium in depicting the state of the nation. Focussing on questions of genre, narrative form, and serialisation, this volume examines the variety of ways in which popular recent British and Irish television series negotiate the concept of community as a key component of the state of the nation.
Keywords: 2000-2099; Great Britain; Ireland; Aufsatzsammlung; Fernsehserie; Irland; Großbritannien